C3 and C4 grass species: who can reduce soil nitrous oxide emissions in a continental arid region? - Ning J; He XZ; Hou F (MDPI AG)
In order to relieve grazing pressure, drought-tolerant grass species are widely cultivated in arid regions. However, soil N emission is largely neglected while pursuing forage yield. We carried out a randomized block study to investigate whether and how the C3 and C4 grass species differ in soil N emission in a typical salinized field with temperate continental arid climate in the northwest inland regions, China. We quantified soil N2O flux from two C3 (barley and rye) and two C4 grass species [corngrass and sorghum hybrid sudangrass (SHS)] in fields during the growing season (from May to September) by using the static box method, and then determined the relationships between soil N2O fluxes and forage yield and soil properties. Results show that soil available nitrogen, soil temperature, pH, soil organic carbon, and total nitrogen were correlated, but soil water was anti-correlated with soil N2O fluxes. In addition, N2O flux increased significantly faster with soil temperature in C4 than in C3 grass fields. Although the lower total N2O emission fluxes were detected for C3 species, the lower yield-scaled N2O was detected for C4 species. Our study provided insights into the determination of grass species and the understanding of mechanisms regulating N2O fluxes in C3 and C4 species in the continental arid regions.
Published source must be acknowledged
Keywords: greenhouse gas; denitrification; soil organic carbon; hay yield; crude protein yield; pasture; 0401 Atmospheric Sciences; 0502 Environmental Science and Management